Prevalence of abnormal amniotic fluid index and its association with maternal and perinatal outcomes: a retrospective observational study - Singh, Vidhi; Srivastava, Shalini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Abnormal amniotic fluid volume is an established indicator of fetal wellbeing and has been linked to increased maternal and perinatal morbidity. Ultrasonographic assessment using the amniotic fluid index (AFI) enables early identification of high-risk pregnancies and guides obstetric decision making. Objectives of the study was to determine the prevalence of abnormal amniotic fluid volume and evaluate its association with adverse maternal and perinatal outcomes. Methods: This retrospective observational study was conducted at a tertiary care teaching hospital and included 300 consecutive singleton pregnancies beyond 28 weeks’ gestation with documented AFI measurements. Amniotic fluid volume was categorized as oligohydramnios (AFI ≤5 cm), normal AFI (5.1–23.9 cm), and polyhydramnios (AFI ≥24 cm). Maternal outcomes assessed included induction of labour, mode of delivery, postpartum hemorrhage, and maternal intensive care unit (ICU) admission. The primary perinatal outcome was a composite of meconium-stained liquor, neonatal intensive care unit (NICU) admission, low Apgar score at 5 minutes (<7), and low birth weight (<2500 g). Statistical analysis included chi square tests and multivariable logistic regression. Results: Of the 300 pregnancies, 240 (80%) had normal AFI, 45 (15%) had oligohydramnios, and 15 (5%) had polyhydramnios. Cesarean delivery was significantly more frequent in pregnancies with abnormal AFI (53.3% in oligohydramnios and 46.7% in polyhydramnios) compared to normal AFI (29.2%; p=0.001). Abnormal AFI was associated with significantly higher rates of meconium-stained liquor, NICU admission, low Apgar score, and low birth weight (all p<0.001). On multivariable analysis, abnormal AFI remained independently associated with adverse perinatal outcomes. Conclusions: Abnormal amniotic fluid volume, particularly oligohydramnios, is associated with increased obstetric intervention and adverse perinatal outcomes. AFI is a simple, non-invasive, and effective tool for identifying high risk pregnancies and optimizing maternal and neonatal care.